(untitled) (Ciudades, 2017)
The Participatory Action Research project "Neighborhoods in Transition" is based on the hypothesis that we need to find meeting points among emerging social processes of socio-ecological transition and the new generation of integrated urban rehabilitation policies that turns itself possible from the Leipzig Charter. The conditions that facilitate the production and social management of habitat should be created by Public Administrations through participatory processes and public-private co-management. “Neighborhoods in Transition” gives theoretical and methodological support to the demand for technical assistance by social organizations in both neighborhoods, based on different priorities.